English With Games - Muhlisa Zohidova Faxritdinovna (Zien Journals, 2023)
The article is dedicated to teaching English through games and with fun. The author mentions that the success of interactive lessons even with games depend on teachers' methodologic, analyzing skills. Students attend actively during the lesson and their progress is evident.
Keywords: Effectiveness of games; method; learner